Depression among the Geriatric Population is a Matter of Concern: A Community Based Study in a Rural Area of West Bengal (Nepal Journal of Epidemiology, 2013)
Background   Depression is commonest psychiatric disorder in elderly; it is often misdiagnosed and undertreated. People with depression suffer from impairment of all major areas of functioning ranging from personal care to social capability, which in turn decreases individuals’ quality of life and increases dependency on others Elderly patients with depression are more prone in developing chronic diseases like ischemic heart disease, diabetes mellitus, hypertension. This problem may be more severe in rural population. Objective of this study is to find out the magnitude of depression and its correlates among a rural geriatric population. Materials and Methods Population based cross sectional study was done in Singur, West Bengal with a sample size of 85 with the help of a pretested semi structured schedule and a geriatric depression scale (short form).  Results Majority 61.2(%) of the study population were in the age group of 60 to 69 years and most belonged to joint Hindu family. Cardiovascular disease (67.05%) especially hypertension followed by musculoskeletal problems (42.35%) were the two major health related conditions suffered by this population and they usually made avail of government health facilities during illness. About 58.8% of the population suffered from depression and this was associated with nuclear family AOR(95%CI)=8.625(1.697-43.831), with poor income AOR(95%CI)=7.628(1.862-31.847), financial dependence AOR(95%CI)=4.948 (1.044-23.554)and living without spouse AOR(95%CI)=7.422 (1.513-36.418) and also presence of disease OR =5.423 (1.348-21.81). Conclusion Alarmingly, the prevalence of depression was observed to be quite high in this rural population and so was prevalence of different morbidities. All these will hasten the isolation of this vulnerable population from general community and increase burden on younger generation. DOI: http://dx.doi.org/10.3126/nje.v3i4.9515 Keywords: